Complexity and the Emergence of Physical Properties - Fuentes, Miguel Angel (2014)
Using the effective complexity measure, proposed by M. Gell-Mann and S. Lloyd, we give a quantitative definition of an emergent property. We use several previous results and properties of this particular information measure closely related to the random features of the entity and its regularities.